2018
DOI: 10.3928/01484834-20180720-08
|View full text |Cite
|
Sign up to set email alerts
|

An Interprofessional Education Simulation Workshop: Health Professions Learning Palliative Care Communication

Abstract: Additional research is needed regarding longitudinal curricular efforts and direct patient care outcomes. [J Nurs Educ. 2018;57(8):493-497.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The participants have found that the simulations have increased their confidence in their own skills (Hovland et al., 2018; Jakobsen et al., 2018; Smith et al., 2018) and helped them prioritize patient needs (Roberts & Goodhand, 2018; Smith et al., 2018). Simulations have also allowed the participants to increase their understanding of the roles and responsibilities of other professionals (Bradway et al., 2018; Costello et al., 2018; Pinto et al., 2018; Wietholter et al., 2017; Zamjahn et al., 2018). Furthermore, interprofessional simulations have developed the participants’ leadership skills (Jakobsen et al., 2018; Pinto et al., 2018) and improved their stress management ability (Jakobsen et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The participants have found that the simulations have increased their confidence in their own skills (Hovland et al., 2018; Jakobsen et al., 2018; Smith et al., 2018) and helped them prioritize patient needs (Roberts & Goodhand, 2018; Smith et al., 2018). Simulations have also allowed the participants to increase their understanding of the roles and responsibilities of other professionals (Bradway et al., 2018; Costello et al., 2018; Pinto et al., 2018; Wietholter et al., 2017; Zamjahn et al., 2018). Furthermore, interprofessional simulations have developed the participants’ leadership skills (Jakobsen et al., 2018; Pinto et al., 2018) and improved their stress management ability (Jakobsen et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…General skills mainly include teamwork, communication, and listening skills. Since palliative and end-of-life care requires a multi-disciplinary team (Hall et al, 2011), the importance of developing teamwork skills was discussed in five papers (Bradway et al, 2018;Bye et al, 2009;Dando et al, 2012;Kaasalainen et al, 2015;Noble et al, 2018), and four papers recognized that each team member needs to be knowledgeable about the roles of other healthcare professionals (Dando et al, 2012;Meredith, 2010;Noble et al, 2018;Wittenberg-Lyles et al, 2014). Healthcare professionals should be able to consult or refer clients to other healthcare professionals and palliative and end-of-life care specialists when necessary (Maher and Mitchell, 2013;Noble et al, 2018).…”
Section: Thematic Analysismentioning
confidence: 99%
“…According to many authors, palliative and endof-life care requires specialized skills, such as communication and listening skills in a context of terminal illness, and how to address psychosocial and spiritual needs (Davis et al, 2013;Dawson and Barker, 1995;Morales-Mart ın et al, 2012;Wilding, 2015;Wittenberg-Lyles et al, 2014). Four papers emphasized that all healthcare professionals who work with dying people should master these skills (Bradway et al, 2018;Bye et al, 2009;Davis et al, 2013;Wittenberg-Lyles et al, 2014).…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Structures used in the acute care setting include but are not limited to: a) Five Wishes (agingwithdignity. org) 100,101 , b) Respecting Choices ® (respectingchoices.org) 77,101,102 , c) the Chronic Care Model which is used also in the acute care setting within the care continuum [103][104][105] , d) components for early integrated PC consultations 106 , e) Clinical Practice Guidelines for Quality Palliative Care in oncology 62 which includes a guidance regarding anticipated disease trajectory and prognosis, f) concurrent or simultaneous care, 14,45,107,108 and g) the "SENS-structure" (which stands for Symptoms, Expectations and end-of-life decisions, Network and Support of the network). 109,110 These structures support the decision making process by anticipating future treatment and care options (ACP), and communicating these through e.g.…”
Section: Guiding Structures For Assessment Planning and Management In Palliative Care Including Advance Care Planningmentioning
confidence: 99%